Effect of contacts with health professionals on modern contraceptives uptake during the first 6 weeks after child birth: a prospective cohort study in Arsi Zone - Gebi Husein Jima; Jelle Stekelenburg; Hailu Fekadu; Tegbar Yigzaw Sendekie; Regien Biesma (BMC, 2023)
Abstract Background Healthy timing and spacing of pregnancy refers to the spacing between deliveries and subsequent pregnancies. The World Health Organization recommends waiting at least 24 months between the date of the live birth and the conception of the subsequent pregnancy in order to lower the risk of unfavorable maternal, perinatal, and newborn outcomes. Low use of contraception contributes to the high level of short inter-pregnancy intervals. Different studies conclusively demonstrate that this is a reality existing in Ethiopia right now. Limited data is available regarding the effects of contacts with health professionals on the use of contraception during the postnatal period. Methods A prospective cohort study was performed from October 01, 2020 to March 01, 2021. The study included 418 postnatal women who gave birth during the previous week. They were followed throughout the full postnatal period. A pre-tested structured questionnaire was used to gather the data. Data were gathered twice: once during the first week following birth and once again from the eighth to the 42nd day after birth. Epi-Info version 7 was used to enter data, which was subsequently exported to SPSS version 21 for analysis. The effect of contacts with health professionals where contraceptives were discussed on contraception uptake was measured using adjusted relative risk and its 95% confidence interval. Results Modern contraceptive uptake rate during the postnatal period was 16% (95% CI: 12.50-19.50%). Contraceptive use was 3.56 times more likely in women who were counseled about contraceptives during a contacts with health professionals at a health facility compared to those who did not have a contact (aRR = 3.56, 95% CI: 1.97-6.32). Women's age, place of residence, knowledge of whether they can become pregnant before menses return, menses return after birth, and resuming sexual activity after birth were all significantly associated with contraceptive use during the first six weeks following child birth. Conclusions Modern contraceptive uptake rate during the postnatal period among women in the study area was low. Contacts with health professionals where contraception is discussed was the main factor associated with contraception uptake during the postnatal period. We recommend that the Arsi Zone Health Office, the Weardas Health Office in the Arsi Zone, and the health care providers in the Arsi Zone health facilities strengthen contraceptive counseling in postnatal health services to reduce the proportion of women with short inter-pregnancy intervals.